Analisis Kebijakan Pasca Bencana Penetapan Relokasi Wajib pada Zona Merah melalui Perspektif Tugas dan Fungsi Pemerintah Daerah Kabupaten Cianjur - Sekha Anggita Maulidina; Dedi Mulyadi; Aji Mulyana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The policy of mandatory relocation in post-disaster areas, particularly in Cianjur's red zones, plays a crucial role in mitigating risks associated with earthquakes and other natural disasters. This study analyzes the implementation of this policy from the perspective of local government tasks and functions, focusing on the coordination of various stakeholders, legal frameworks, and community involvement. The research uses a qualitative approach, combining legal-normative and sociological perspectives to explore the challenges and conflicts faced during the relocation process. Findings indicate that while the policy has been crucial in safeguarding public safety, its implementation has faced significant challenges such as budget constraints, community resistance, and logistical issues. The study highlights the importance of improving collaboration among local authorities, security agencies, and affected communities. The findings also suggest the need for a more transparent and inclusive approach to policy implementation, ensuring the protection of displaced populations' rights.